Upaya Berbasis Sekolah Peningkatan Hemoglobin dalam Masa Menstruasi Remaja Putri : Studi di SMP 113 Jakarta - Vivi Silawati; Apriliani Kartika Sari (Jurnal Sosiologi Andalas, 2020)
One of the problems experienced by young women is anemia during menstruation. Iron (Fe) supplementation can be used to improve their hemoglobin status. The problem is that many young women do not know this and therefore do not take iron (Fe) supplements to solve anemia problems. One effort that can be done is giving iron (Fe) supplements in schools. This article presents the results of research on efforts to provide iron (Fe) supplements in schools to young women when menstruating. The research question is what programs can be done in schools to provide iron (Fe) supplements to young women who experience anemia due to menstruation. Using a quasi-experimental method, the results showed that giving iron (Fe) supplements to adolescent girls who had anemia due to menstruation could be done at school: after the officers gave iron supplements (Fe) there was a significant difference in hemoglobin levels before and after being given Fe tablets in theexperimenttal group (p. <0.05), and there was a significant difference in hemoglobin levels in the case and control groups (p <0.05). Routine administration of Fe tablets every week in processing is effective in increasing hemoglobin levels in adolescent girls.